2022
DOI: 10.3389/fimmu.2022.918314
|View full text |Cite
|
Sign up to set email alerts
|

Immune Evasion and Drug Resistance Mediated by USP22 in Cancer: Novel Targets and Mechanisms

Abstract: Regulation of ubiquitination is involved in various processes in cancer occurrence and development, including cell cycle arrest, cell proliferation, apoptosis, invasion, metastasis, and immunity. Ubiquitination plays an important role not only at the transcriptional and post-translational levels but also at the protein level. When ubiquitination is in a pathological state, abnormally activated biological processes will not only induce cancer progression but also induce immune evasion. The main function of deub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 111 publications
0
25
0
Order By: Relevance
“…Therefore, novel treatments for metastatic KIRC still need to develop and explore. Studies have indicated that USPs are pivotal for cancer progression, and several USPs have been utilized as targets to develop inhibitors for cancer prevention [ 18 , 24 , 25 ]. ML364 is a small molecule inhibitor of the deubiquitinase USP2, which could degrade CCND1 and prevent cancer cell cycle progression in colorectal cancer [ 26 ]; USP7 could induce apoptosis in multiple myeloma cells resistant to conventional and bortezomib therapies [ 27 ]; Developing the medicines based on the USPs are considered as a potential new treatment for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel treatments for metastatic KIRC still need to develop and explore. Studies have indicated that USPs are pivotal for cancer progression, and several USPs have been utilized as targets to develop inhibitors for cancer prevention [ 18 , 24 , 25 ]. ML364 is a small molecule inhibitor of the deubiquitinase USP2, which could degrade CCND1 and prevent cancer cell cycle progression in colorectal cancer [ 26 ]; USP7 could induce apoptosis in multiple myeloma cells resistant to conventional and bortezomib therapies [ 27 ]; Developing the medicines based on the USPs are considered as a potential new treatment for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…USP22 is highly expressed in various tumours such as lung ( 72 ), colorectal ( 73 ) and gastric cancers ( 74 ), and is involved in DNA transcription, malignant transformation of cells and cell cycle progression ( 75 ).…”
Section: Abnormally Expressed Usps In Tumour Cellsmentioning
confidence: 99%
“…The programmed death receptor 1 (PD-1) has been reported in several studies to mediate resistance to immune attack in cancer ( 207 209 ). The programmed death ligand 1 (PD-L1)/ubiquitin-specific protease 22 (USP22) axis has been found to control tumor immune escape ( 210 212 ). USP22 is considered to be an oncogene and can enhance the stability of substrate proteins through the inhibition of proteasomal degradation ( 213 ).…”
Section: Exosomal Long Non-coding Rnas and Different Gi Cancersmentioning
confidence: 99%